Counseling and Therapy – Recent Developments in Theories and Practices: edited by Kenjiro Fukao, London, United Kingdom, intechOpen, 2022, 194 pp., ISBN 978-1-80355-575-1, http://doi.org/10.5772/intechopen.98103. - Apriatama, Dony; Sulistiawan, Hendra (British Journal of Guidance & Counselling, 2026)
The book *Counseling and Therapy – Recent Developments in Theories and Practices*, edited by Kenjiro Fukao, examines contemporary advancements in psychotherapy and counselling, emphasizing the need for flexible, culturally sensitive approaches to address diverse client needs in a changing world. It explores innovative theories such as mixed methods research, a novel happiness theory linking Aristotle’s ethics with evolutionary science, and the General Three-Component Structural-Dynamic Theory of Psychotherapy, alongside practical adaptations like integrating religious beliefs into Rational-Emotive Behavior Therapy and culturally tailored mindfulness-based stress reduction. The text also highlights alternative modalities such as nature-based therapy and addresses the impact of the COVID-19 pandemic on mental health services, particularly in African contexts, including the role of volunteer counselling networks. Overall, the book provides mental health professionals with theoretical insights and practical strategies to enhance therapeutic effectiveness amid global and cultural challenges.